PENGARUH ATRIBUT PRODUK DAN KUALITAS LAYANAN TERHADAP KEPUTUSAN PEMBELIAN PRODUK FASHION DI MEDIA SOSIAL FACEBOOK - Irma Sri Wahyuni; Hayat Yusuf; Sinarwati Sinarwati; Nasrul Nasrul; Sudirman Zaid (Jurusan Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Halu Oleo, 2022)
This study aims to determine: (1) the influence of product attributes towards purchase decision of fashion products at online shop through social media Facebook, (2) the influence of service quality towards purchase decision of fashion products at online shop through social media Facebook, and (3) the influence of product attributes and service quality simultaneously towards purchase decision of fashion products at online shop through social media Facebook. This research takes 90 samples from the customer of the ofmanagement student, economics and bussiness faculty halu oleo university. The analysis technique used is multiple linear regression and uses the help of the IBM SPSS version 16 application using a standard significance of 5%. Based on the results of the analysis in this study, it can be concluded that product attributes and service qualitytogether have a positive and significant effect on purchasing decision, product attributes has a positive and significant effect on purchasing decision and Service Quality has a significant positive effect on Purchasing Decision.